8.3: Distinguished Paper: Next‐Generation Display Technology: Quantum‐Dot LEDs. Issue 1 (June 2015) - Manders, Jesse R.; Qian, Lei; Titov, Alexandre; Hyvonen, Jake; Tokarz‐Scott, Jean; Xue, Jiangeng; Holloway, Paul H.
Abstract : Colloidal quantum dot‐based hybrid light‐emitting diodes (QDLEDs) have been demonstrated that exhibit quantum efficiencies >10% for all three fundamental colors (>18% for green), device lifetimes of >280K hours, extremely well‐tuned color fidelity approaching Rec. 2020 specifications, and complete solution processing to fabricate devices. The extremely desirable properties of color tunability/fidelity, long lifetime, and low cost processing from solutions makes QD‐LED technology disruptive and will lead to next generation displays.